PENINGKATAN KUALITAS LITERASI GENERASI MUDA MELALUI PELATIHAN EXTENSIVE READING BAGI PARA VOLUNTER NGO MENGAJAR DI PONTIANAK - Anistya Fitri Larasati; Melti Oktavianda; Meizi Fahrizal; Dedi Herdiansyah; Januardi M. Diah; Charlyna S. Purba; Urai Muhani; Henrian Stiawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance the foreign language literacy capacity of NPO Aku Belajar volunteers in Pontianak through training based on Extensive Reading (ER), addressing the low literacy and foreign language skills in Indonesia, particularly among volunteers assisting children from underprivileged families. The methods applied include participatory workshops, hands-on practice, continuous mentoring, and evaluation through pre-tests, post-tests, observations, and ER reading product assessments. The results show significant improvements in ER concept understanding (10% → 100%), training material relevance (20% → 90%), ability to identify new methods (25% → 95%), participants’ reading interest (60% → 80%), and high participant satisfaction (average 4.4/5). ER training effectively enhances volunteers’ foreign language literacy while facilitating the production of educational reading materials for marginalized children, creating a domino effect in improving community education quality. The program demonstrates the flexibility and adaptability of ER in nonformal education, strengthens partnerships between academic institutions and community organizations, and contributes to the achievement of SDG 4 (quality and inclusive education) and SDG 10 (reduced inequalities). These findings confirm that interest-based and practical interventions can serve as a best practice strategy to improve literacy, volunteer capacity, and cross-community educational empowerment.